Summertime Politics: Cultural Resurgence, Resource Sovereignty, and the Aasivik Movement - Norman, David (Études Inuit Studies, 2023)
While Home Rule negotiations between Kalaallit Nunaat and Denmark were underway, the Aasivik summer festivals, founded in 1976, proposed an alternative model of collective politics. Borrowing its name from a term for historical gathering sites, the modern Aasivik movement hosted debates on a wide range of topics, bringing political activity into settlements and camps. Although Aasivik’s influence on Kalaallit Nunaat’s political history has been widely recognized, the movement’s theoretical complexity has gone largely unacknowledged. In this article, I discuss several key episodes from the festival’s first decade, emphasizing how Aasivik mobilized cultural heritage as a means of responding to social inequalities introduced by Danish colonial rule. First, I outline Aasivik’s roots in local and global Indigenous decolonial movements and describe how these influences led activists to analyze topics such as dispossession, labor, Marxist thought, and collective land access in the festival’s early debates and public statements. I then examine how the presence of customary performance and avant-garde theater at several Aasiviit intersected with the movement’s political positions, focusing on the activities of the Tuukkaq Theater and the revitalization of uaajeerneq (mask dancing). Finally, I discuss the significance of Aasivik’s land-based model of politics for contemporary debates in Indigenous critical theory.